2019
DOI: 10.1186/s13075-019-2035-3
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and elevation of anti-citrullinated protein antibodies prior to the onset of rheumatoid arthritis

Abstract: BackgroundAnti-citrullinated protein antibodies (ACPA) are central to rheumatoid arthritis (RA) pathogenesis and may develop at inflamed mucosa. We investigated whether asthma, a disease of airway mucosal inflammation, was associated with elevated ACPA before RA diagnosis.MethodsWe performed a nested case-control study among women in two prospective cohorts, the Nurses’ Health Study (NHS; 1976–2014) and NHSII (1989–2015). Blood was obtained on a subset (NHS: 1989–1990; NHSII: 1996–1999). Cases met 1987 ACR or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…The primary finding that a history of respiratory disease was associated with developing RA aligns with the growing body of evidence supporting a connection between the lungs and RA. The association between chronic lower respiratory diseases and overall RA risk is consistent with existing data for asthma (9)(10)(11)(12)(13)(14)(15)18,19,25), COPD (10,(15)(16)(17)20), and ILD (27,28), which is mixed but mostly positive. Novel to our analysis were the associations between RA and acute upper respiratory diseases (e.g., sinusitis and pharyngitis), chronic upper respiratory diseases (e.g., rhinitis), and acute lower respiratory diseases (e.g., influenza and pneumonia), which have never been reported.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The primary finding that a history of respiratory disease was associated with developing RA aligns with the growing body of evidence supporting a connection between the lungs and RA. The association between chronic lower respiratory diseases and overall RA risk is consistent with existing data for asthma (9)(10)(11)(12)(13)(14)(15)18,19,25), COPD (10,(15)(16)(17)20), and ILD (27,28), which is mixed but mostly positive. Novel to our analysis were the associations between RA and acute upper respiratory diseases (e.g., sinusitis and pharyngitis), chronic upper respiratory diseases (e.g., rhinitis), and acute lower respiratory diseases (e.g., influenza and pneumonia), which have never been reported.…”
Section: Discussionsupporting
confidence: 88%
“…In newly diagnosed RA as well as RA prior to clinical diagnosis, smoking has been associated with citrullination and production of ACPAs in the lungs in the presence of subtle airway abnormalities, but in the absence of diagnosed airway disease (21)(22)(23). Other studies have demonstrated increased citrullination and/or ACPA production in patients with COPD (24), asthma (25), and interstitial lung disease (ILD) (26), also in the absence of smoking. These studies raise the question as to what extent the association between airway disease and RA may be attributable to smoking as a common risk factor and to what extent airway disease confers a risk of RA in the absence of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The biologic effect of smoking or other inhalants on RA risk may be due to induction of local pulmonary mucosal inflammation at the bronchioles and alveoli, leading to protein citrullination, loss of immune tolerance, and the apparent formation of ACPA preceding RA symptoms. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several recent epidemiologic studies have also identified significant increases in the prevalence of lung disease, particularly AD, during pre‐RA, supporting lung disease as a risk factor for developing RA . Specifically, Zaccardelli et al found that a clinical diagnosis of asthma was present in 18% of serum ACPA + subjects who later developed classified RA compared to only 6% in matched controls.…”
Section: The Lung In Pre‐ramentioning
confidence: 98%
“…70 Several recent epidemiologic studies have also identified significant increases in the prevalence of lung disease, particularly AD, during pre-RA, supporting lung disease as a risk factor for developing RA. 29,87 Specifically, Zaccardelli et al 87…”
Section: The Lung In Pre-r Amentioning
confidence: 99%